Debate: Severe bicuspid aortic valve stenosis in non-high-risk surgical patients. In favor of surgery - Jacobo Silva Guisasola (REC: Interventional Cardiology (English Ed.), 2022)
QUESTION: What is the prevalence of bicuspid aortic valve in the population currently eligible for surgical aortic valve replacement? ANSWER: The prevalence of bicuspid aortic valve is around 1% to 2% of the population. Somewhere between 27% and 35% of the population will eventually require surgery at the 20-year follow-up.1 On the other hand, the associated dilatation of the ascending aorta, with conflicting results regarding its prevalence, stands at around 50% to 80%.1 At our center, 30% of all aortic valve replacements or repairs—with or without replacement of the ascending aorta—are performed on the bicuspid aortic valve. Also, this is a group of predominantly male patients with a mean age of 55 years, and different clinical features compared to the aortic stenosis described in elderly patients. Many of these patients are repaired when regurgitation is predominant with excellent clinical outcomes. Q.: What special considerations should be made with surgery when performed on the bicuspid aortic valve? A.: There are 3 special considerations that should be observed. In the first place, this condition affects a group of younger patients. Also, these valves have severe calcification posing great technical difficulties regarding decalcification for correct implantation under direct vison. On many occasions, eventually, the ascending aorta...